Management of Academic Services at the Faculty of Social Sciences and Government Sciences UIN Ar-Raniry Banda Aceh - Marwan R; Nasir Usman; Khairuddin Khairuddin (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2024)
Academic service management is the management of all activities carried out in academics to provide services to students to achieve organizational goals. The research objective is to determine academic service management, and obstacles and improve the quality of academic services at the Faculty of Social Sciences and Government Sciences, UIN Ar-Raniry. This research uses a descriptive qualitative approach because this research aims to understand an interaction situation in academic services, namely to get an overview of academic service management at the Faculty of Social and Governmental Sciences (FISIP) UIN Ar-Raniry Banda Aceh. Data collection techniques are observation, interviews, and documentation. Data analysis uses qualitative descriptive analysis with data reduction, presentation, and conclusion-drawing techniques. The results of the research, (1) academic service management is under Standard Operational Procedures (SOP) and receives direct supervision from faculty leaders; (2) there are still problems such as unstable electricity, network errors, officer discipline; (3) efforts to improve the quality of academic services by trying to provide excellent service through recording attendance lists; serving registration according to procedures and without favoritism, printing KRS and KHS, giving directions, getting around so as not to clash with lecture schedules; dress neatly to facilitate the implementation of student exams.